Responsible Governance of Tribal Public Health Data: Data Sharing Ethics and Common Challenges in the US Public Health System - Alec J Calac; Luis R Gasca; William H Swain (Journal of Medical Internet Research)
AbstractIn their viewpoint, Schmit and colleagues thoughtfully discuss tribal public authority, as well as barriers and facilitators to the responsible use of data generated by or collected from members of sovereign American Indian and Alaska Native Nations. Key topics not covered by the authors that warrant discussion include tribal public health workforce development, data systems infrastructure, and federal facilitation of tribal self-governance programs. These additional topics will better contextualize the ethical, legal, and social issues specific to American Indian and Alaska Native public health practice.